Research on game scheduling of galvanizing pipe production - Yingying Li; Shaohua Dong (Functional Materials, 2017)
In this paper, we analyze and integrate the production process of "hot-dip galvanized steel pipe", the main product in the case enterprise and builds a model for the production scheduling with Cooperative Game Theory from the perspective of the enterprise. In order to get the Optimal Game Scheduling Solution, Genetic algorithm is used and Shaply value thought and β rule allocation method are combined to solve the problem of increased profit allocation in different customers. And fair and reasonable allocation mechanism is of great significance to the stability of the coalition and enterprise development.